IMPLEMENTASI SISTEM PENILAIAN UJIAN SEMESTER DI SDN 01 BILAH HULU MENGGUNAKAN METODE RABIN-KARP - Waluyo, Bambang (Lambung Mangkurat University, 2023)
In the world of education, assessment is very important when the process of learning activities has been completed. Based on the results of observations made by researchers at SDN 01 Bilah Hulu, there are often several obstacles where the teacher sometimes takes a lot of time to check essay answers, the more exams and students who take the exam, the more exams the teacher will correct. This causes a decrease in the quality of the evaluation and sometimes the evaluation is no longer objective. So that it causes variations in the assessments in the class given by different human assessors, which are felt by students as a source of injustice. The purpose of this study is to create an automatic scoring system for semester exam answers on web-based essay questions and to build a web-based semester exam results scoring system by applying the Rabin-Karp method. The results of the web-based essay assessment process are in the form of student values that have been summarized by the system. The automatic essay exam scoring system using the Rabin-Karp algorithm was tested on 57 students in two classes, namely 28 students in class VI-A with the average score from the teacher manually being 82.64 and the average score of the automatic system being 81.17 . Meanwhile, in class VI-B with 29 students, the manual average was 75.34 and the automatic system average was 76.48.